Kondisi dan Pengelolaan Kawasan Hulu DAS Belawan Hubungannya dengan Tingkat Bahaya Erosi pada Lahan Budidaya di Kabupaten Deli Serdang - Anggy Palleriani Harahap; Abdul Rauf; Miswar Budi Mulya (Fakultas Teknik, 2021)
The Belawan watershed is located at Deli Serdang Regency and Medan City, with mountainous terrain (70.58%), hills (35.15%), and slopes (20.28%). This study aims to identify the risk of erosion of cropland, especially coffee, corn, and chocolate, to identify more appropriate erosion control measures to achieve regional protection objectives . The research was conducted in the upstream Belawan watershed in the Sibolangit, Bandar Baru, and Kutalimbaru regions from September 2020 to December 2020. The magnitude of the erosion hazard value is analysed using the USLE approach . The USLE method on the amount of erosion is determined by 5 (five) factors, these factors are the rainfall erosion factor (R); soil erodibility factor (K); vegetation factor (C); conservation factor (P) and topography factor (LS). The erosion rate valuefor land use types varies from 95.27 tons/Ha.yr to 232.43 tons/Ha.yr. The amount of erosion that can be tolerated in land use for coffee, corn, and cacao ranges from 19.94 tons/Ha.yr to 39.79 tons/Ha.yr. The risk level for erosion in coffee areas 4.83 and 10.86 with high criteria and very high criteria; in areas of corn event 6.29 and 8.38 with high criteria and in brown areas 5.24 and 3.88 with high criteria and medium criteria.